2018
DOI: 10.1016/j.bbr.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and dynamic functional neural connectivity in children and adolescents

Abstract: Our results provide new evidence that mindfulness in youth relates to functional neural dynamics and interactions between neurocognitive networks, over time.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 42 publications
4
65
1
Order By: Relevance
“…Of note, even prior to ME-ICA denoising, head motion was relatively low across the sample (see Table 1 ). For participants in the higher range of motion, ME-ICA sufficiently flattens out the DVARS trace (i.e., rate of change of BOLD signal across the entire brain at each time point; Power et al, 2012 ), see Marusak et al (2017) for demonstration. Additionally, mean FD was not related to our main variable of interest, trait resilience ( r = 0.16, p = 0.27), nor depressive symptoms ( r = −0.04, p = 0.76).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, even prior to ME-ICA denoising, head motion was relatively low across the sample (see Table 1 ). For participants in the higher range of motion, ME-ICA sufficiently flattens out the DVARS trace (i.e., rate of change of BOLD signal across the entire brain at each time point; Power et al, 2012 ), see Marusak et al (2017) for demonstration. Additionally, mean FD was not related to our main variable of interest, trait resilience ( r = 0.16, p = 0.27), nor depressive symptoms ( r = −0.04, p = 0.76).…”
Section: Methodsmentioning
confidence: 99%
“…2 ). Templates and further details regarding component identification is described in detail in our prior work ( Marusak et al, 2016 , 2017 ). Observed group aggregate spatial maps of the 5 components of interest ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ischemic stroke, accounts for 80% of stroke, which is mainly caused by an insufficient supply of glucose and oxygen to central nervous system (CNS) tissue and thus resulting in a significant amount of cell damages [2]. A series of complex cellular and biochemical molecular mechanisms are involved in the pathology, such as the excitotoxicity, mitochondrial dysfunction, ionic imbalance, oxidative stress, and inflammation, eventually leading to a loss of neurological functions and even cell death [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can then be probed for association with measures of inter-or intra-individual differences (e.g. (Beaty, et al 2018;Marusak, et al 2018;Vidaurre, et al 2017b)). State-based approaches can differ in whether they assume smooth transitions between states (Allen, et al 2014;Ou, et al 2015) or instantaneous reconfigurations Yaesoubi, et al 2018), their focus on a particular signal domain (e.g.…”
Section: Example 1: Data-driven Models Of Tvcmentioning
confidence: 99%
“…Despite these challenges, many fundamental questions about the relationship between TVC and ongoing cognition necessitate the application of these methods, and there exists an emerging literature demonstrating their feasibility and utility (Kucyi, et al 2018b). Numerous studies suggest that BOLD TVC is associated with a variety of "spontaneous" cognitive dynamics including memory reactivations (Tambini and Davachi 2013), variations in perceptual performance Thompson, et al 2013a), changes in arousal indexed by pupil diameter (Shine, et al 2016a), and self-reported stimulus-independent thoughts (Chou, et al 2017;Kucyi and Davis 2014;Kucyi, et al 2013;Marusak, et al 2018;Mittner, et al 2014). Although these studies did not all include 'pure rest' conditions, the types of cognitive processes they investigated are all likely to fluctuate during typical wakeful rest.…”
Section: Bold Tvc and "Spontaneous" Cognition During The Resting Statementioning
confidence: 99%